Comparison of Estrogen Î² Receptor Expression and the Addition of Various Dose of Geistein to HUVEC Endothel Cell which Exposed to Oxidative Stress - Handayani, Vera (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To compare Î² estrogen receptor on HUVEC endothelial for each Genistein dose addition with Î²-estradiol physiologic dose. Methode: Experimental study performed in Physiology Laboratorium, Medical Faculty of Brawijaya University Malang, HUVEC culture exposed by glucose as a dysfunction endothelial model. Endothel collected from female newborn umbilicus was cultured to make a confluent culture. The culture was divided into 7 groups: 1. HUVEC without treatment, 2. HUVEC + glucose 33 mM, 3. HUVEC + glucose 33 mM + 17Î² estradiol , 4. HUVEC + glucose 33 mM+ Genistein 2.5 Î¼m. 5. HUVEC + Glucose 33 mM + Genistein 5 Î¼m, 6. HUVEC + Glucose 33 mM + Genistein 7,5 Î¼m, 7. HUVEC + Glucose 33 mM + Genistein 10 Î¼m. Culture then was incubated in 37Â°C and stained with immunohistochemistry, using primary antibody of Î² estrogen receptor. The expression was observed on the -15, 30, 60, 120 and 240th minute. The datas from observation result was analysed with ANOVA test and correlation test. Result: Estrogen receptor comparison between group 1 was significantly different with group 2, 3, 6, 7 and not significantly different with groups 4, 5. Estrogen receptor between group 2 was significantly different with group 4, 5 but not significantly different with groups 3, 6, 7. Estrogen receptor comparison between group 3 was significantly different with group 4, 5 and not significantly different with groups 6, 7. Estrogen receptor comparison between group 4 was significantly different with group 6, 7 and not significantly different with groups 5. Estrogen receptor comparison between group 5 was significantly different with group 6, 7. Estrogen receptor comparison between group 6 was not significantly different with group 7. Isoflavon Genistein dose increase on 30, 60 dan 120 minutes will reduce Î² estrogen receptor expression on endothelial HUVEC and on 15 and 240 minutes shows that there was no significant correlation with Î² estrogen receptor expression on endothel HUVEC. Conclusion: There was significant expression distinction of ERÎ² in glucose induced HUVEC exposed by 17Î² estradiol compared with those exposed by Genistein but not in Genistein dose 7.5 and 10 Î¼m. The lower of Isoflavon Genistein dose in the -30, 60 dan 120 minute will cause expression of Î² estrogen receptor in HUVEC endothelial cell that tends to be higher. [Indones J Obstet Gynecol 2010; 34-1:24-30] Keywords: Î² estrogen receptor, HUVEC, genistein, estradiol.